2006
DOI: 10.1243/09544054jem416
|View full text |Cite
|
Sign up to set email alerts
|

Tool-Life Modelling of Carbide and Ceramic Cutting Tools Using Multi-Linear Regression Analysis

Abstract: This paper presents a study for the development of tool-life models for machining operations by means of a statistical approach called multi-linear regression analysis. The study was applied to a milling process for machining SAE 121 cast iron in a factory without interrupting the mass production. Different cutting tool materials under dry conditions were used in the cutting tests. Several machining experiments were performed and mathematical models for tool life have been postulated by using least-square regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…C is thus a system parameter that is a function of an arbitrarily selected tool life T and determines the nature of the solution of equation (8). According to the Cardano method used to solve cubic equation 24 , by expedient transformation equation (10) can be brought to the form…”
Section: For Cutting With Cbn Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…C is thus a system parameter that is a function of an arbitrarily selected tool life T and determines the nature of the solution of equation (8). According to the Cardano method used to solve cubic equation 24 , by expedient transformation equation (10) can be brought to the form…”
Section: For Cutting With Cbn Toolsmentioning
confidence: 99%
“…In the case of v min = v max , given the situation p = q = 0, the function T-v also has an inflection, which can be calculated from the second differential quotient of Function (1): Figure 11. Structure of the solutions of equation (8).…”
Section: For Cutting With Cbn Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general method of empirical model is to use the tools with specific materials and geometric parameters to conduct milling experiments on a certain kind of difficultto-machine material workpiece under certain milling conditions and obtain a large number of experimental data. The undetermined coefficients are determined by statistical method [63,64]. The establishment process of empirical model is shown in Figure 4.…”
Section: Process Of Modelingmentioning
confidence: 99%
“…With the rapid development of ceramic materials [12], ceramic cutting tools have shown outstanding advantages for many applications. The superior hardness of ceramics can improve the wear resistance of cutting tools when machining workpieces with high hardness [13]. A study on the friction coefficient of ceramic tools for wood-based materials concluded that the friction coefficient of an Al 2 O 3 matrix composite ceramic tool does not exceed 0.3, which is less than the 0.45 of popular hard metal tools [14].…”
Section: Introductionmentioning
confidence: 99%